Understanding Earth–: Ocean Processes using Real-time Data from NEPTUNE, Canada’s Widely Distributed Sensor Networks, Northeast Pacific - Barnes, Christopher; Best, Mairi; Pautet, Lucie; Pirenne, Benoît (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2011)
SUMMARY After several years of planning, NEPTUNE Canada [www.neptunecanada.ca], as part of the Ocean Networks Canada Observatory, largely completed the installation of the world’s first regional cabled observatory network in 2009. The 800 km cable loop west of Vancouver Island connects five nodes in coastal, continental slope, abyssal plain and spreading-ridge environments. Abundant power and high-bandwidth communications support a network of hundreds of sensors that deliver data and imagery in real- or near real-time, and will transform our knowledge of the ocean environment and interacting processes. With the world’s oceans and climate in a state of crisis, the development of cabled observatory technologies is most timely and offers a growing data archive of unparalleled importance for new discoveries.